2004
DOI: 10.1152/ajpendo.00464.2003
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocellular lipid content in type 2 diabetes patients compared with overweight sedentary men and highly trained endurance athletes

Abstract: Recent evidence suggests that intramyocellular lipid (IMCL) accretion is associated with obesity and the development of insulin resistance and/or type 2 diabetes. However, trained endurance athletes are markedly insulin sensitive, despite an elevated mixed muscle lipid content. In an effort to explain this metabolic paradox, we compared muscle fiber type-specific IMCL storage between populations known to have elevated IMCL deposits. Immunofluorescence microscopy was performed on muscle biopsies obtained from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
177
5
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(201 citation statements)
references
References 73 publications
18
177
5
1
Order By: Relevance
“…As elevated IMTG accretion in type 2 diabetic patients is the result of a structural imbalance between NEFA uptake, IMTG deposition and its subsequent mobilisation and/or oxidation [21][22][23], it has been suggested that an elevated IMTG turnover rate can prevent excessive accumulation of intramyocellular FA metabolites [9, 10, 13-16, 44, 45] and/or reduce the degree of intramyocellular lipid peroxidation [17]. In agreement, interventions known to Fig.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…As elevated IMTG accretion in type 2 diabetic patients is the result of a structural imbalance between NEFA uptake, IMTG deposition and its subsequent mobilisation and/or oxidation [21][22][23], it has been suggested that an elevated IMTG turnover rate can prevent excessive accumulation of intramyocellular FA metabolites [9, 10, 13-16, 44, 45] and/or reduce the degree of intramyocellular lipid peroxidation [17]. In agreement, interventions known to Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Multiple serial sections (5 μm) were thaw-mounted together on uncoated, pre-cleaned glass slides for each subject. To determine muscle fibre type specific IMTG content, cross-sections were stained with oil red O together with immunolabelled cellular constituents using a previously described protocol [23,25,41]. For each muscle biopsy, a total of 84±4 muscle fibres were analysed for lipid content.…”
Section: Muscle Sample Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple serial sections (5 μm) were thaw-mounted together on uncoated, precleaned glass slides for each subject. To determine muscle fibre type-specific IMTG content, cross-sections were stained with Oil red O together with immunolabelled cellular constituents using a protocol described before [2]. For each muscle biopsy a total of 58±7 and 49±4 muscle fibres were analysed for lipid content for diabetes patients and control subjects respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Disturbances in fatty acid metabolism, as found in sedentary, obese and/or type 2 diabetes patients, are an important factor in the development of skeletal muscle insulin resistance [1][2][3]. Elevated fatty acid delivery and/or impaired fatty acid oxidation result in net intramyocellular accumulation of triacylglycerol and fatty acid metabolites (such as fatty acyl-CoA, ceramides and diacylglycerol).…”
Section: Introductionmentioning
confidence: 99%